Results of selfmonitoring on glucometer systems Advance and Optium in daily routine - Chlup, Rudolf; Payne, Martin; Zapletalová, Jana; Komenda, Stanislav; Doubravová, Blanka; Reznícková, Martina; Chlupová, Ludmila; Seckar, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2005)
The aim of this prospective clinical study was to compare the results of B-glucose estimations performed simultaneously on glucometer Advance (with Micro-draw strips) and Optium (G3 strips) by lay healthy volunteers under non-standardized conditions of everyday life, to assess the difficulties dealing with lay-handling of these systems and to demonstrate the possibilities of the software Glucobalance (Hypoguard) and PC-Link (Medisense/Abbott) for the analysis of selfmonitoring. In the course of 5 days, a total of 721 pairs of measurements were carried out on 10 pairs of glucometer Advance and Optium by 10 healthy volunteers aged 16-40 years. The data transfer of all values into computer from glucometer Advance using the Glucobalance software and from glucometer Optium using the PC-Link was carried out to determine the results. The correlation of B-glucose measured on the glucometer Advance and Optium was strong (r = 0.73). Glucometer Advance brings values about 0.21 +/- 0.06 mmol/l lower than glucometer Optium. The average difference found within each pairs of glucometers Advance - Optium varied. Nevertheless, these differences are acceptable for routine selfmonitoring. The handling of glucometer Advance is not difficult for lay persons. The Glucobalance software simplifies the result evaluation by each tested person. Even though there are some advantages in comparison with the PC-Link, it should be further developed.
Keywords: mladiství; krevní glukóza; reagenční papírky; Adult; Reagent Strips; lidé; dospělí; Blood Glucose; Blood Glucose Self-Monitoring; selfmonitoring glykemie; Humans; Adolescent